Analisis Kelayakan Finansial dan Sensitivitas Usahatani Buah Naga dengan Penyinaran Ultraviolet - Rahmat, Agne; Tedjaningsih, Tenten; Djuliansah, Dedi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Dragon fruit is a comodity that has good opportunities and prospects in the horticulture subsector. A farmer in Cilangkap Village use ultraviolet light in the process of cultivating dragon fruit to increase productivity. The use of ultraviolet light will affect the costs and revenues of dragon fruit farming. The aim of this research is to determine the financial feasibility and sensitivity of dragon fruit farming with ultraviolet light. Research location in the Cilangkap Village, Manonjaya District, Tasikmalaya Regency. The method used is a case study of a dragon fruit farmers with location selection and respondent determination carried out deliberately or purposive sampling. The research results show an NPV value of Rp. 3,773,325,000. Net B/C 6.9, IRR 49,07 percent, and payback period 3 years 9 month. Sensitivity analysis on a increase in operational costs of 30 percent obtained results showing an NPV value of Rp. 3,510,693,471. Net B/C 6.2, IRR 47,21 percent, and payback period 4 years 0.5 month. Sensitivity analysis on a 20 percent reduction in production quantity obtained results showing an NPV value of Rp. 2,560,393,679. Net B/C 4.8, IRR 41,26 percent, and payback period 4 years 6 month. The results showed that dragon fruit farming with ultraviolet light is worth to pursuing and continuing.